Supply chain management : an introduction to logistics - Waters, C. D. J. [ (C. Donald J.)] , 1949- (Palgrave Macmillan, 2009)
A broad general introduction to all essential aspects of logistics and supply chain management, set within the wider business context. The book uses well-developed pedagogy and numerous case studies, guiding the reader through the subject by retaining a strong focus on the application of theory and practical situations